Enzymatic responses in the head and midgut of Africanized Apis mellifera contaminated with a sublethal concentration of thiamethoxam - Decio, Pâmela [UNESP]; Miotelo, Lucas [UNESP]; Pereira, Franco Dani Campos [UNESP]; Roat, Thaisa Cristina [UNESP]; Marin-Morales, Maria Aparecida [UNESP]; Malaspina, Osmar [UNESP] (Elsevier, 2021)
The increasing use of insecticides, promoted by the intensification of agriculture, has raised concerns about their influence on the decline of bee colonies, which play a fundamental role in pollination. Thus, it is fundamental to elucidate the effects of insecticides on bees. This study investigated the damage caused by a sublethal concentration of thiamethoxam - TMX (0.0227 ng/μL of feed) in the head and midgut of Africanized Apis mellifera, by analyzing the enzymatic biomarkers, oxidative stress, and occurrence of lipid peroxidation. The data showed that the insecticide increased acetylcholinesterase activity (AChE) and glutathione-S-transferase (GST), whereas carboxylesterase (CaE3) activity decreased in the heads. Our results indicate that the antioxidant enzymes were less active in the head because only glutathione peroxidase (GPX) showed alterations. In the midgut, there were no alkaline phosphatase (ALP) or superoxide dismutase (SOD) responses and a decrease in the activity of CaE was observed. Otherwise, there was an increase in GPX, and the TBARS (thiobarbituric acid reactive substances) assay also showed differences in the midgut. The TBARS (thiobarbituric acid reactive substances) assay also showed differences in the midgut. The results showed enzymes such as CaE3, GST, AChE, ALP, SOD, and GPX, as well as the TBARS assay, are useful biomarkers on bees. They may be used in combination as a promising tool for characterizing bee exposure to insecticides.
Keywords: Biomarkers; Honeybees; Neonicotinoid; Oxidative stress